IMPOLITENESS AS A PERSUASIVE TOOL IN SOCIAL MEDIA POITICAL DISCUSSIONS - Mukhammadiyeva Munisa Bakhodir qizi; M.J.Isroilova (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
This article investigates impoliteness as a persuasive communicative strategy in political discussions on social media platforms. Drawing on pragmatic and discourse-analytical approaches, particularly the theories of impoliteness developed by Culpeper and Bousfield, the study examines how face-threatening and aggressive language is strategically employed to influence audiences, delegitimize political opponents, construct group identities, and mobilize political support. The article argues that impoliteness in online political discourse should not be interpreted merely as a violation of communicative norms, but rather as a purposeful rhetorical resource reinforced by the affordances of digital media. While impoliteness increases visibility, emotional engagement, and persuasive impact, it simultaneously contributes to polarization and the deterioration of deliberative democratic communication.